2022
DOI: 10.26434/chemrxiv-2022-3cr9k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cu+ transient species mediate Cu catalyst reconstruction during CO2 electroreduction

Abstract: Understanding metal surface reconstruction during operation is of the uttermost importance in heterogeneous catalysis as it directly affects the available active sites. However, surface reconstruction is notoriously difficult to study because of the dynamic nature of the phenomena behind it. Here, we report on the mechanism and the intermediates, which drive the rearrangement of copper catalysts during the electrochemical CO2 reduction reaction. In-situ methods, including mass spectrometry and fluorescence spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…This hypothesis is in line with the high-intensity signals we observed in the carbonate and CO Raman regions as well as the boosted activity for CO at low overpotentials (see Figure S21). Furthermore, copper carbonate transient species were elucidated through in situ fluorescence spectroscopy, and the authors invoked these transient copper carbonate complexes as highly active phases for CO formation in a dissolution–redeposition mechanism, in line with our findings . We therefore ascribe the low-overpotential CO 2 -to-CO activation observed in our combined PE and TR-SERS experiments to an alternative reaction pathway that involves malachite copper carbonate hydroxide complexes in the electrolyte solution, which generates a highly active site upon redeposition and subsequent reduction.…”
Section: Resultssupporting
confidence: 84%
“…This hypothesis is in line with the high-intensity signals we observed in the carbonate and CO Raman regions as well as the boosted activity for CO at low overpotentials (see Figure S21). Furthermore, copper carbonate transient species were elucidated through in situ fluorescence spectroscopy, and the authors invoked these transient copper carbonate complexes as highly active phases for CO formation in a dissolution–redeposition mechanism, in line with our findings . We therefore ascribe the low-overpotential CO 2 -to-CO activation observed in our combined PE and TR-SERS experiments to an alternative reaction pathway that involves malachite copper carbonate hydroxide complexes in the electrolyte solution, which generates a highly active site upon redeposition and subsequent reduction.…”
Section: Resultssupporting
confidence: 84%
“…However, a study suggests that surface-bound CO 2 RR intermediates (e.g., *CO and *C 2 O 4 ) can enhance the dissolution of Cu surface atoms, which would be minimized under N 2 conditions. 33 A similar observation of CO 2 RR intermediates enhancing the degradation of the catalyst surface has been reported on Au NPs. 7 These previous ndings suggest that Cu dissolution is not a major factor in the enhanced declustering observed under Ar conditions.…”
Section: Resultssupporting
confidence: 73%
“…Recently, the group of Buonsanti , showed that Cu dissolves under negative applied potentials, with subsequent redeposition on the electrode roughening the electrocatalyst surface. Based on their results, we hypothesize that this dissolution can be promoted by small amounts of oxygen in the system as they show that the dissolution is enhanced in air . Even though CO 2 is being purged throughout the experiment, we cannot guarantee that the cell is completely oxygen-free.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their results, we hypothesize that this dissolution can be promoted by small amounts of oxygen in the system as they show that the dissolution is enhanced in air. 62 Even though CO 2 is being purged throughout the experiment, we cannot guarantee that the cell is completely oxygen-free. At higher temperatures, surface diffusion of the copper atoms is expected to be enhanced.…”
Section: Resultsmentioning
confidence: 99%